Factors Associated with Abnormal Uterine Bleeding in Perimenopausal Women - Radenko Ivanović; Bojan Joksimović; Vladimir Čančar; Helena Marić; Draženka Matović; Nenad Lalović; Radiša Pavlović; Miloš Milosavljević; Jovana Milosavljević; Slobodan Janković (Clinical and Experimental Obstetrics & Gynecology)
Background: Abnormal uterine bleeding (AUB) is one of the most common health problems encountered in women of the perimenopausal age group. The aim of this study was to investigate the characteristics of functional AUB in perimenopausal women, and to identify predictors of the occurrence of functional AUB in perimenopausal women. Methods: This was a cross-sectional study that included 45 women with complaints of AUB admitted to the gynecology ward in the University Hospital in Foča, and 45 women without AUB who underwent a gynecological examination in the Primary Health Center in Foča, Bosnia and Herzegovina. We included women with AUB who had a normal ultrasound finding without obvious genital or cervical lesions, and who were not on hormonal therapy. The existence of AUB was determined on the basis of a clinical examination by a gynecologist and existing medical documentation. A logistic regression model was used to assess the possible relationship between the occurrence of the functional AUB and the risk factors for its occurrence. Results: The mean patient age was 48.38 ± 2.40 years. There was no significant difference in age, frequency of physical activity, or previous use of oral contraceptives between the two groups of patients divided by the presence of the functional AUB in perimenopause. The logistic regression model showed that age (p = 0.008), high values of body mass index (BMI) (p = 0.001), consumption of alcohol and cigarettes on a daily basis (p = 0.001), and hypertension (p = 0.046) represented significant risk factors associated with functional AUB in perimenopausal women. Conclusions: During routine exams of women approaching menopause, gynecologists should emphasize the harms of smoking and alcohol use, as well as the significance of non-pharmacological and pharmacological methods for the treatment of obesity and hypertension.